this Perancangan Media Pembelajaran Berbasis Android Menggunakan Microsoft Powerpoint Berbantukan Fitur Ispring Suite pada Mata Pelajaran IPA di SMP Negeri 1 Banuhampu - Nurleni; Supriadi, Supriadi; Okra, Riri; Derta, Sarwo (Indonesian Research Journal on Education, 2023)
This research is based on the students' low understanding of the mastery of bold science learning materials due to the absence of interesting learning media that will increase students' learning motivation. This study aims tocreate learning media in the form of a Mobile Application in *.apk format that can be run on Android Smartphones related to science subjects for class VIII semester 2 at SMPN 1 Banuhampu that are valid, practical, and effective. The method used in this study is the ADDIE version of the Research and Development (R&D) research method which consists of analysis, design, development, implement, evaluation, and theLuther-Sutopo multimedia development model which consists of six stages, namely the concept, design, material stages. collection, assembly, testing, and distribution. The product test of this research is in the form of a validity test conducted by 4 experts calculated using the Aiken's V Statistics formula, a practicality test by 1 material expert calculated using the Kappa Moment formula, and an effectiveness test by 15 class VIIIstudents at SMP N 1 Banuhampu who calculated using the statistical formula of Richard R. Hake (G-Score). The assessment instrument is in the form of a 5-scale questionnaire. Based on the test of the product that has been carried out by the author, the results of the analysis of the product validity test with an average value of 0.84 with very valid criteria, practicality with an average value of 0.88 with very high criteria, and an effective test with an average value of 0 .91 with Very Effective Criteria. After receiving the award, it is hoped that from the results of the learning media test, this learning media can help teachers and students in carrying out the teaching and learning process.